Method Development and Validation for Simultaneous Determination of Ezetimibe and Simvastatin In Combined Pharmaceutical Dosage Form By RP-HPLC Method - Krishnaveni, G; Sathyannarayana, PVV (International Journal of Pharmaceutical and Life Sciences, 2013)
A simple, rapid reverse phase high-performance liquid chromatographic method was developed and validated for the simultaneous estimation of Ezetimibe and Simvastatin in bulk and pharmaceutical dosage forms. Chromatography was carried out by using Chromosil C-18,column having 250 x 4.6mm internal diameter with a mixture of Methanol:Acetonitrile:0.1%Orthophosphoric Aid in the ratio of 75:20:05 (v/v/v) as mobile phase. Determination of the different analytical parameters such as linearity, precision, accuracy, and specificity, limit of detection (LOD) and limit of quantification (LOQ) was done. The calibration curve was found to be linear for each analyte in the desired concentration range. The average recovery was found to be 99.88 and 100.12 for Ezetimibe and Simvastatin respectively. The proposed method is highly sensitive, precise and accurate, which was evident from the LOD value of 1.2ppm and 0.25ppm for Ezetimibe and Simvastatin respectively and hence the present method can be applied successfully for the quantification of active pharmaceutical ingredient (API) content in the combined formulations of Ezetimibe and Simvastatin. DOI: http://dx.doi.org/10.3329/ijpls.v2i2.15450 International Journal of Pharmaceutical and Life Sciences Vol.2(2) 2013: 60-69